Differences in attitude towards cadaveric organ donation: Observations in a multiracial Malaysian society - Loch, A.; Hilmi, I.N.; Mazam, Z.; Pillay, Y.; Choon, D.S.K. (Medcom Ltd, 2010)
Background: Willingness to donate organs is affected by socio-cultural and religious values. The Malaysian society is made up of three ethnic groups: Malay, Chinese, and Indian, with Islam, Buddhism and Hinduism as their religions respectively. This study examined the knowledge and perception towards organ donation for each group. Methods: This study was conducted at University Malaya Medical Centre, Kuala Lumpur, Malaysia. Relatives of patients awaiting treatment at the emergency department answered a questionnaire on knowledge and attitude on organ transplantation. Results: A total of 904 questionnaires were completed; 90.6% would accept organs, 43.6% would donate, and 4.0% carried donor cards. The reasons for reluctance to donate included: fear of organs being used for research (18.8%), desire to be buried whole (18.0%), fear of less active treatment if patient is known to be a donor (12.8%). Malays were less willing to accept organs from a different race (63.5%) compared to Chinese (83.3%) and Indians (83.8%) (OR=0.35, 95%CI: 0.23-0.54 and OR=0.34, 95%CI: 0.22-0.51 respectively) and also less likely to donate organs (29.8%) as compared to Chinese (42.1%) and Indians (63.2%) (OR=0.57, 95%CI 0.40-0.83 and OR=0.24, 95%CI 0.17-0.35 respectively). Malays were less willing to donate organs to another race compared to Chinese or Indians (OR=0.48, 95%CI 0.33-0.70 and OR=0.22, 95%CI 0.15-0.31 respectively). Only 34.7% of Muslims are aware of fatwa supporting organ donation. Conclusions: The awareness of organ donation was low. Clear differences exist among ethnic groups. Cultural-religious attitudes and lack of trust in the medical systems were reasons for reluctance to donation. Identifying socio-cultural barriers and reassuring donors regarding medical care are required. (Hong Kong j.emerg.med. 2010;17:236-243)